Diversity of Sweet Corn Canopy Architecture for Intercropping Pattern Suitability with Cayenne Pepper - Patandean, Brayen; Chozin, Muhamad Achmad; Ritonga, Arya Widura (Department of Agronomy and Horticulture, IPB University, 2025)
The intercropping system has become increasingly important due to the limited availability of agricultural land and the growing population. Sweet corn is one of the potential crops for intercropping; however, its compatibility with companion plants varies among genotypes. This study analyzed the canopy diversity of 10 sweet corn genotypes and their impact on temperature, humidity, and light intensity. The research was conducted at the Pasir Kuda Experimental Station, Bogor Agricultural University, from June to August 2024, using ten hybrid sweet corn genotypes in a randomized complete block design with three replications. Each genotype was planted in plots measuring 3.75 m², with a 25 cm × 75 cm spacing, resulting in 30 plants per bed. Principal Component Analysis (PCA) and hierarchical analysis identified three clusters of genotypes based on ten morphological traits. The first cluster included “Verona”, “Talenta”, “Paragon”, SM12 x SB13, “Exotic”, and “Secada”. The second cluster consisted of “Arinta”, SB8 x SM6, and SM12 x SM1, while the third cluster included SM1 x SM9. Temperature and humidity measurements revealed significant differences among clusters, influencing photosynthetic efficiency and yield potential. Denser canopies exhibited lower temperatures, higher humidity, and reduced light intensity, whereas more open canopies displayed higher temperatures, lower humidity, and increased light intensity. The study also analyzed cob weight, length, and diameter, as well as critical factors for yield potential and photosynthetic efficiency. Based on the results, genotypes with denser canopies from Cluster One (“Verona”, “Talenta”, “Paragon”, SM12 x SB13, “Exotic”, and “Secada”) are recommended for intercropping with cayenne peppers due to their favourable microclimate compatibility.